Epigenetic Control of Plant Response to Heavy Metal Stress: A New View on Aluminum Tolerance - Gallo-Franco, Jenny Johana; Sosa, Chrystian Camilo; Ghneim-Herrera, Thaura; Quimbaya, Mauricio (Frontiers in Plant Science, 2020)
Heavy metal (HM) ions represent an agronomic problem for crop production in acid soils (pH≤5). Although low concentrations of some HMs, such as copper (Co), iron (Fe), and zinc (Zn), are essential for plant physiology and development, at high concentration HMs result in morphological and physiological damage for plants. Aluminum (Al3+) is one of the most abundant and toxic chemical elements in acid soils, and plants have evolved different mechanisms to handle its negative effects, that can be grouped into two main categories: (i) exclusion mechanisms, that avoid or minimize the entrance of Al3+ to plant roots, and (ii) detoxification mechanisms, allowing Al3+ sequestration/translocation and detoxification once it is integrated into the cellular environment. Several studies have elucidated the genetic mechanisms that confer aluminum tolerance to plants, reporting specific genetic elements involved in this positive response, focusing on plants genetic adaptation to stress. In contrast epigenetic mechanisms underlying plant responses to HM stress, particularly to aluminum toxicity, remain poorly understood. Here, we describe the principal epigenetic mechanisms related to crop responses to HM ions, with special focus on aluminum tolerance. Additionally, using rice as a study case, we evaluated and proposed novel candidate genes as possible key regulators in the epigenetic response to aluminum stress tolerance.